2005
DOI: 10.1080/15732480500247694
|View full text |Cite
|
Sign up to set email alerts
|

Interactive horizontal load model for pedestrians crossing footbridges

Abstract: In recent years several theories have been put forward in relation to lateral forces imparted on bridges from crowd movements. It is now widely accepted that the interaction between the crowd and the structure, particularly when the crowd pacing frequency is close to the lateral natural frequency, is the major factor determining the lateral response. However, very little work has been done with individual pedestrians in order to determine the relationship between the lateral force induced by a single pedestria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…These parameters have been much-investigated in biomechanical engineering applications using measurements of rigid surface walking forces and accelerations of the human body centre of mass ( [25], [26], [27], [28], [29],[30], [31]). For structural vibration, Archbold [32], Caprani et al [33], Archbold et al [34], and Ahmadi et al [13] adopted the MSMD model parameters from the biomechanics literature. Hashim et al [35] determined dynamic properties of the standing (stationary) human body.…”
Section: Models For Pedestriansmentioning
confidence: 99%
“…These parameters have been much-investigated in biomechanical engineering applications using measurements of rigid surface walking forces and accelerations of the human body centre of mass ( [25], [26], [27], [28], [29],[30], [31]). For structural vibration, Archbold [32], Caprani et al [33], Archbold et al [34], and Ahmadi et al [13] adopted the MSMD model parameters from the biomechanics literature. Hashim et al [35] determined dynamic properties of the standing (stationary) human body.…”
Section: Models For Pedestriansmentioning
confidence: 99%
“…This GRF can be represented as a Fourier series (Bachmann & Ammann 1987;Rainer et al, 1988). However, in this work, each pedestrian is described by a moving force with just the first harmonic of the Fourier series (Archbold 2004) and is thus given by the following:…”
Section: Single Pedestrian Force Modelmentioning
confidence: 99%
“…Therefore, a human can be modelled as a moving springmass-damper (MSMD) to account for human mass, stiffness, and damping effects on the structural system. The MSMD was introduced by Archbold [10] and [11] into the HSI area. Archbold [11] also found that the MF model is conservative as it does not consider interaction between the pedestrian and the moving bridge, while Clemente et al (2010) [12] showed that if the interaction between the pedestrian and the bridge is to be considered, the pedestrians should be modelled as SMD oscillators.…”
Section: Introductionmentioning
confidence: 99%